KARAKTERISTIK ORGANOLEPTIK SUP JAGUNG INSTAN YANG DIPERKAYA TEPUNG CANGKANG TELUR BEBEK - fakhrissal dian arga nugroho; siti aminah; afrilia afriatul lael; neneng indarti (Jurnal Pangan dan Gizi, 2020)
Duck eggshell flour which contains a source of calcium which is useful for increasing calcium in the body, eggshell flour as an addition to instant corn soup enriched with duck eggshell flour. This research method is an experimental method using a completely randomized design (CRD) method. Utilization of duck eggshells made in the form of flour as a mixture of food products including instant soup. Ingredients that can be used as instant soup are sweet corn. Instant corn soup has good nutrition and distinctive characteristics. So, instant corn soup can be enriched in its nutritional content (calcium) by adding calcium from duck eggshell flour. The purpose of this research is to find out the Organoleptic characteristics (color, flavour, texture and taste) instant corn soup enriched with duck eggshell flour. This research uses RAL method which consists of 5 treatments, namely the addition of 0%, 5%, 10%, 15% and 20% duck eggshell flour which is then analyzed. The results showed instant corn soup enriched with duck eggshell flour had a different effect on the addition of eggshell flour, the sensory properties of the most preferred taste was 5%.